Attempts to harmonise the European Union legislation in respect of employee representation in corporate governance bodies - Rudolf, Stanisław (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: Representation of employees in corporate governance bodies is, on the one hand, an important element in the democratisation of labour relations, while on the other hand, it can bring notable positive benefits to businesses. It is standard practice in a decided majority of the old EU countries, but only to a limited extent does it function in the countries which joined the EU in 2004 and later. Aim: The author of the article has defined two important goals. The first one is to present solutions concerning employee representation in individual EU countries. The second goal is to present earlier attempts to harmonise the EU legislation on the matters of such representation and to indicate the possibility of such harmonisation under the current conditions. Results: What has been noted in the article is that as many as 10 EU countries have no legislation concerning employee representation in corporate bodies. Although such legislation exists in other countries, the implemented solutions are heavily diversified. It has also been evidenced that the past attempts aimed to harmonise this sphere have generally failed. Against such background, establishing what is commonly referred to as a European Company with employee representation in its corporate governance bodies should be considered as a success, but due to a very limited range of such companies, it is but a partial success.